Nivel de conocimiento del personal de enfermería en reanimación cardiopulmonar avanzada en pacientes críticos - Quilligana Reinoso, Mariela Beatriz (2025)
Advanced cardiopulmonary resuscitation (ACPR) for critically ill patients focuses on a group of medical techniques and procedures designed to restore cardiac and respiratory functions in patients experiencing cardiac or respiratory arrest. Therefore, this study aims to determine the nursing staff's knowledge level in advanced cardiopulmonary resuscitation for critically ill patients. A quantitative approach methodology was used, as surveys were applied, and data were utilized to assess the nursing staff’s level of knowledge in advanced cardiopulmonary resuscitation for critically ill patients. This study is supported by applied and descriptive research, with the questionnaire serving as the instrument for data collection. The questionnaire was administered to nursing staff in the emergency unit of a hospital. Among the main findings, it was highlighted that the level of knowledge among nursing staff in advanced cardiopulmonary resuscitation for critically ill patients is variable, with a majority demonstrating confidence in their skills but a fraction exhibiting a lack of preparation in key aspects of the procedure. This may be influenced by practical experience, training frequency, and exposure to emergency scenarios. The study concludes that teamwork and effective communication have been identified as fundamental factors in performing ACPR in the intensive care unit. However, differences in staff opinions may present a potential risk, as they can impact synchronization and coordination during ACPR execution.